The General Orders of the Board of Supervisors, City and County of San Francisco 13 (1869) - (:unkn) unknown (My University, 1869)
Prohibited the discharge of any cannon within the city, in the part of the county between Larkin and Ninth streets, or in the streets forming the water. Violators fined not less than one hundred dollars or imprisoned not more than thirty days.
Keywords: DISCHARGE